Investigating the Factors that Affect Structural Integrity of Buildings Under Construction in Kampala Region. - Tusingwire, Moses (Kabale University, 2025)
The construction in Uganda contributes up 12% to the country’s Gross domestic product. It’s a vibrant sector that employs many skilled and unskilled youth in the country. The acute need for housing and other infrastructure to spike up and push forward the country’s vision of 2040 and the millennium development goals makes construction a major sector of focus. However, this in Uganda is being challenged with poor integrity of structures leading to failure and collapse of many structures. This collapse happens 6 (Six) times on average yearly prompting the need to research on what causes this loss of structural integrity. This research has through a literature review identified three elements of Material quality, workmanship quality, and methods of executing work to be assessed for being the influencing factor to structural integrity loss. Ways to enhance the integrity of structures have also been identified and stated in this report. The material was acquired through observation, sampling, and focused discussion as well as secondary information on sites about test results, and local authority checks. Data collected was analyzed using Excel to generate histograms, charts, and descriptive statistical information.